Elucidating the direct effects of the novel HDAC inhibitor bocodepsin (OKI-179) on T cells to rationally design regimens for combining with immunotherapy - Holay, Nisha; Somma, Alexander; Duchow, Mark; Soleimani, Milad; Capasso, Anna; Kottapalli, Srividya; Rios, Joshua; Giri, Uma; Diamond, Jennifer; Schreiber, Anna; Piscopio, Anthony D.; Van Den Berg, Carla; et al. (Frontiers in Immunology, 2023)
Histone deacetylase inhibitors (HDACi) are currently being explored for the treatment of both solid and hematological malignancies. Although originally thought to exert cytotoxic responses through tumor-intrinsic mechanisms by increasing expression of tumor suppressor genes, several studies have demonstrated that therapeutic responses depend on an intact adaptive immune system; particularly CD8 T cells. It is therefore critical to understand how HDACi directly affect T cells in order to rationally design regimens for combination with immunotherapy. In this study, we evaluated T cell responses to a novel class-selective HDACi (OKI-179, bocodepsin) by assessing histone acetylation levels, which revealed rapid responsiveness accompanied by an increase in CD4 and CD8 T cell frequencies in the blood. However, these rapid responses were transient, as histone acetylation and frequencies waned within 24 hours. This contrasts with in vitro models where high acetylation was sustained and continuous exposure to HDACi suppressed cytokine production. In vivo comparisons demonstrated that stopping OKI-179 treatment during PD-1 blockade was superior to continuous treatment. These findings provide novel insight into the direct effects of HDAC inhibitors on T cells and that treatment schedules that take into account acute T cell effects should be considered when combined with immunotherapies, to fully harness the tumor-specific T cell responses in patients.